Transforming a company’s staffing process: implementing E-recruitment - Monteiro, Ileana (2020)
This project discusses the importance of evaluating a company's staffing methods, in order to improve and optimize people recruitment, selection, as well as integration and socialization in the organization. The particular focus is the implementation of Social Media (SM) and e-recruitment in a private sector company, reveling the importance of these digital media to recruit candidates with the desired profile and to support the new collaborators' integration and socialization. A business project is presented, following a scientific-technical approach, in the analysis of functions and in the profiles definitions and on information obtained through semi-structured interviews with human resources specialists who are responsible for recruitment and selection as well as interviews with newly hired workers in the company, demonstrating the effectiveness of these means for jobseekers. At the same time, a project study for the implementation of new digital tools in the company is prepared. This study shows that the development of a new website articulated with SM, for which business pages have been built, in addition to the use of e-recruitment portals, is a real benefit for the organization because they facilitate and increase the performance of the recruitment and selection process at the same time promoting the company's image.